2010
DOI: 10.1111/j.1369-7625.2010.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and clinicians’ research priorities

Abstract: Background If research addresses the questions of relevance to patients and clinicians, decision-makers will be better equipped to design and deliver health services which meet their needs. To this end, a number of initiatives have engaged patients and clinicians in setting research agendas. This paper aimed to scope the research literature addressing such efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
142
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(149 citation statements)
references
References 24 publications
3
142
0
4
Order By: Relevance
“…Instead, these efforts have focused on describing the methods of generation and prioritization of research questions. 6 As a result, it is unclear how well the questions that have been published or otherwise made widely available reflect the views of those on the front lines of health care delivery, who are key stakeholders and anticipated consumers of comparative effectiveness research.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…Instead, these efforts have focused on describing the methods of generation and prioritization of research questions. 6 As a result, it is unclear how well the questions that have been published or otherwise made widely available reflect the views of those on the front lines of health care delivery, who are key stakeholders and anticipated consumers of comparative effectiveness research.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…To become more responsive to patients' needs, it would be vital to involve patients in identifying priorities. Patients' ''experiential knowledge'', can complement scientific or medical knowledge [3,5,6]. Secondly, the process itself becomes more democratic [2,5].…”
Section: To the Editorsmentioning
confidence: 99%
“…Participants were advised to contact investigators as soon as they developed symptoms of a cold or a worsening of their chest disease and reviewed in 48 h. Acute exacerbations were defined when any four of the 12 items of the Fuchs' criteria were present [5]. At each visit, spontaneous sputum was sent for quantitative microbiology [6] and two throat swabs were performed using a semi-nested PCR for influenza A and B, respiratory syncytial virus (RSV), rhinovirus (RV), coronavirus, human metapneumovirus, parainfluenza 1, 2 and 3, and adenovirus [7] and RV were sequenced [8]. When data were normally distributed, differences were analysed using a non-paired t-test and, when not normally distributed, a non-parametric equivalent.…”
Section: To the Editorsmentioning
confidence: 99%
“…Further, our completion rate is typical of internet surveys that target samples representing the population on key demographic criteria. 26,41,42,43 Although individuals who earn less and have less formal education were under-represented, bivariate analyses demonstrated that the attitudes and beliefs examined did not differ significantly along these characteristics (data not shown). Further, our findings on the predictors of reduced obligations to participate in WG/ES-based NBS were based on a smaller sub-sample of 472 and should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 95%